2012
DOI: 10.3389/fnins.2012.00135
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Transcriptional Factor Dysregulation in the Dorsal Raphe Nucleus of Patients with Major Depressive Disorder

Abstract: Extensive evidence implicates dysfunction in serotonin (5-HT) signaling in the etiology of major depressive disorder (MDD). Dorsal raphe nucleus (DR) is a major source of serotonin in the brain, and previous studies have reported within it alterations in 5-HT-related gene expression, protein levels, receptor binding, and morphological organization in mood disorders. In the present study, we utilized in situ hybridization-guided laser capture microdissection to harvest tissue samples from the middle-caudal subr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 104 publications
3
23
0
Order By: Relevance
“…Chronic stress results in long-lasting chromatin modifications that increase the repression of plasticity-related genes (2-4). In particular, egr1 has been reported to be downregulated in mice stressed by chronic social defeat and in postmortem brains of depressed human subjects, suggesting a pathogenic role for this down-regulation (4,31). In this regard, it is conceivable that repeated LSD1 up-and neuroLSD1 downregulation in response to chronic stress could induce H3K4 hypomethylation at the egr1 promoter (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Chronic stress results in long-lasting chromatin modifications that increase the repression of plasticity-related genes (2-4). In particular, egr1 has been reported to be downregulated in mice stressed by chronic social defeat and in postmortem brains of depressed human subjects, suggesting a pathogenic role for this down-regulation (4,31). In this regard, it is conceivable that repeated LSD1 up-and neuroLSD1 downregulation in response to chronic stress could induce H3K4 hypomethylation at the egr1 promoter (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Whether and how chronic regimens of vmPFC DBS induce neuroplasticity in the 5-HT system is not known. Because previous studies have indicated that depression and suicide in humans (15-18) and depressive-like symptoms in animals (19-21) are accompanied by maladaptive plasticity in the 5-HT system, we hypothesized that stable neuroplastic changes in the 5-HT system may coincide with the antidepressant-like effect of chronic vmPFC DBS.…”
Section: Introductionmentioning
confidence: 99%
“…GATA1: a new transcriptional repressor of synaptic genes associated with depression Although brain imaging studies and postmortem analyses has provided much valuable information about major depression, the molecular determinants of the pathogenesis of major depressive disorder are still unknown. In the past decade, comprehensive analyses of the molecular mechanisms involved in major depression have been performed, largely consisting of high throughput analysis on postmortem brain tissues from patients with major depression (Sibille et al 2004;Kang et al 2007Kang et al , 2012Tochigi et al 2008;Kerman et al 2012;Goswami et al 2013;Medina et al 2013). Major depression is a heterogeneous disease caused by the complex interaction of genes and environmental factors.…”
Section: Neuronal Atrophy and Loss Of Volume In Major Depressive Disomentioning
confidence: 99%